Study on Perioperative Management of Blood Pressure and Effects of Anaesthesia in Hypertensive Patients Undergoing General & Orthopaedic Surgery - Muhammad Naeem, Fazal Wadood, Usman Zeeshan, Salman Shaukat, Muhammad Baqir Ali Khan, Zulquernain Ahmed Zoak (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: During anesthesia, hypertension is the most common additional risk factor that contributes to higher mortality rate. Antihypertension medicine’s withdrawal might leads to symptoms such as anxiety, rebound hypertension, myocardial infarction, tachyarrhythmia, angina exaggeration, and sudden death. The present study aimed to assess the perioperative management of blood pressure and effects of anesthesia in hypertensive patients undergoing general and orthopedic surgery. Patients and Methods: This cross-sectional study was carried out on 162 hypertensive patients in the General Surgery and Orthopedics Units of Khyber Teaching Hospital, Peshawar for the duration from April 2022 to September 2022. Study protocol was approved by institute ethical committee. Patients aged 16 to 70 years of either gender underwent general surgery and orthopaedic surgery were enrolled. The data was acquired during the anesthetist’s initial visit to the operated hypertensive patients’ 24 hour postoperative period. Antihypertensive medications, hemodynamics, anesthesia drugs, fluid use, and blood loss were main variables noted. Heart rate, systolic blood pressure, and diastolic blood pressure were Intraoperative hemodynamics. SPSS version 27 was used for data analysis. Results: Of the total 162 hypertensive patients, there were 68 (42%) male and 94 (58%) females. The overall mean age was 58.62±8.4 years. Before surgery, about 119 (73.5%) patients took antihypertensive medication whereas 124 (76.5%) had antihypertensive medication within 24 hours. The most prevalent antihypertensive medication used and most common class during postoperative management was Calcium channel Blockers and Amlodipine. The most prevalent used anesthetic drug use was Bupivacaine. The incidence of Systolic Blood Pressure (SBP) fall and rise was found in 28 and 6 patients respectively. The incidence of Diastolic Blood Pressure (DBP) fall and rise during intraoperative management was 11 and 8 patient respectively. Conclusion: The present study found that a decreased heart rate in patients who were taking beta blockers consistently. Those who took diuretics had greater DBP and HR at the completion of the procedure. There was no significant change in hemodynamic parameters with any other antihypertensive treatment. Keywords: Hypertension, General Surgery, Orthopaedic, Hemodynamics